(untitled) (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
High soil salinity considered a negatively impacts the growth and productivity of economic crops. Therefore, it is crucial to find solutions that adapt plants to salt stress using eco - friendly practices. the aim of this study to produce vermicompost using Eisenia fetida and palm fronds and a mixture of sheep manure and determine the effect of vermicompost on the germination and growth parameters of tomato plants under salt stress. The vermicompost product revealed a moderate pH of 7.57,EC of 1.66 mS/cm, high levels of organic matter, Carbon, Nitrogen, Phosphorus and Potassium. The study was conducted under a greenhouse in two trials. the first experiment results showed an increase in germination rate, hypocotyl length, and radicle length when tomato seeds it were soaked in a 100% Solution vermicompost extract at a salinity level of (50mmol/L). In the second, irrigating the trays soil with a 100% vermicompost extract at a salinity level of (50 mmol/L ) resulted in a significant increase in seedling length, number of branches, fresh weight and total chlorophyll content compared to the treatment with only the saline solution. The results show that vermicompost plays an important role in mitigating the negative effects of salinity levels not exceeding (50 mmol/L).